Analisis Perbandingan Kepuasan Nasabah Sebelum dan Saat Diberlakukannya Pembatasan Sosial Berskala Besar Pada Bank Nagari - Riche Fermayani; Romi Rianto Harahap; Ega Danu Gusti (Jurnal Ecogen, 2022)
This study objectives to analyze the comparison of customer satisfaction before and during lockdown at Bank Nagari Main Branch Padang. Samples of this studied were 100 respondens who were customers of Bank Nagari in Padang.  Analysis used the paired sample t test with results conclude for the customer satisfaction variable, explain a difference in customer satisfaction before and during lockdown as indicated the value of significancy is 0.000 < 0.05. The customer satisfaction variable can be concluded that there is a difference in customer satisfaction based on the dimensions of tangible before and during lockdown because the value of significance is 0.010 < 0.05. The customer satisfaction variable can be concluded that there is a difference in customer satisfaction based on the reliability dimension before and during lockdown it indicated by a significance of value is 0.040 < 0.05. The customer satisfaction variable that can be concluded there is a difference in customer satisfaction based on the responsiveness dimension before and during lockdown by a significance value is 0.030 < 0.05. The customer satisfaction variable indicated that there is a difference in customer satisfaction based on the assurance dimension before and during lockdown obtained a significance value is 0.000 < 0.05. The customer satisfaction variable can be concluded that there is a difference in customer satisfaction based on the empathy dimension before and during lockdown because the significance value is 0.000 < 0.05. This indicates that the implementation of the lockdown adjustment policy in providing services to customers has reduced customer satisfaction based on the empathy dimensionKeywords: Customer Satisfaction, Tangible, Reliability, Responsiveness, Assurance, And Empathy